2021
DOI: 10.13031/trans.14341
|View full text |Cite
|
Sign up to set email alerts
|

Cattle Feeding Experiment and Chopping Device Parameter Determination for Mechanized Harvesting of Forage Rape Crop

Abstract: HighlightsForage rape crop could effectively alleviate the lack of green forage for livestock in winter.With the growth of forage rape crop, stem lignification was exacerbated and its palatability degenerated.The relationship between particle length and palatability was explored in a cattle feeding experiment.Optimal working parameters of the chopping device were obtained for harvesting the crop in different stages.Abstract. Forage rape crop, which uses the immature plant leaf and stem of a hybrid rape crop (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…When the rotational speed of the cutting roller and its outer diameter were constant, the straw length decreased gradually with an increase in the number of teeth in the multi-edged toothed cutter [44][45][46] . Jing [47] suggested that the theoretical width of plastic tearing should be consistent with the tooth width of the counter-roll plastic tearing machine, and the theoretical length of plastic tearing has a certain functional relationship with the number of teeth, the top diameter and bottom diameter of the tearing knife, as follows:…”
Section: Structure Characteristics Of Multi-edge Toothed Cuttermentioning
confidence: 99%
“…When the rotational speed of the cutting roller and its outer diameter were constant, the straw length decreased gradually with an increase in the number of teeth in the multi-edged toothed cutter [44][45][46] . Jing [47] suggested that the theoretical width of plastic tearing should be consistent with the tooth width of the counter-roll plastic tearing machine, and the theoretical length of plastic tearing has a certain functional relationship with the number of teeth, the top diameter and bottom diameter of the tearing knife, as follows:…”
Section: Structure Characteristics Of Multi-edge Toothed Cuttermentioning
confidence: 99%
“…In the aspect of improving feeding technology, taking the horizontal four-rollers feeding device as the research object, the researches mainly focus on the selection of roller diameter, roller tooth, and optimal design of roller speed [5][6][7][8][9] , the matching of the speed characteristics of the front, middle and rear feeding rolls [10][11][12][13] . However, the research on structural innovation of feeding devices to solve the problem of blockage has not been found.…”
Section: Introductionmentioning
confidence: 99%